Evaluation of the Reality of the Management and Treatment of Solid Waste in Al-Yarmouk Teaching Hospital - Yaseen AL Kindi, Ghayda; ., . (International Journal of Engineering and Technology, 2018)
The aim of this study is to evaluate the reality of the management and treatment of solid waste in Al-Yarmouk teaching hospital, it’s observed that total generation rate of solid waste per day was 116.133 kg/day. while the rate of medical waste generation was 55.075 kg/day. More than 50% of this waste was generated in the surgery rooms and patients' rooms. As well as, it was found that the generation rate of waste for each bed per day was (0.87) kg, while it was (0.28 kg/bed.day) of medical solid waste. In addition, the medical wastes characteristics are studied by taking samples during 3 months of 2017, and analyzing them to determine their moisture content and density. The moisture content are observed between (1.7-30%, 40-56%) for medical and general waste respectively. While the density are (270.4 and 239), kg/m3 for medical and general waste respectively. In addition, the number of surgical operations and the number of patients per day are shown to be most important factors affecting the generation rate of medical waste in the hospital. The treatment of medical wastes for Al-Yarmouk Hospital adopts a system of steam sterilization in a special system.
Keywords: general waste; hospital; medical waste; shredder and Sterilization method; total waste.